A Cyclic (Alkyl)(boryl)germylene Derived from a Cyclic (Alkyl)(amino)germylene. (23rd October 2019) - Rao, Bin; Kinjo, Rei
Abstract: A cyclic (alkyl)(amino)germylene undergoes a ring expansion reaction with dibromomesitylborane (MesBBr2 ) to afford a six‐membered dibromogermane derivative. In the presence of Lewis bases (PMe3 or Me NHC), reduction of the latter with two equivalents of potassium graphite (KC8 ) gives rise to cyclic (alkyl)(boryl)germylene–Lewis base adducts. Upon heating, the germylene—PMe3 adduct reacts with H2 to yield a germane, probably via a base‐free germylene featuring a small HOMO–LUMO gap. Abstract : Die Ringerweiterung eines fünfgliedrigen cyclischen (Alkyl)(amino)germylens mit einem Dihaloboran gefolgt von Reduktion in Gegenwart einer Lewis‐Base führt zu sechsgliedrigen Addukten zwischen einem (Alkyl)(boryl)germylen und der Lewis‐Base. Beim Erwärmen isomerisieren diese zu cyclischen (Alkyl)(germyl)germylenen mit η 3 ‐Koordination oder reagieren auch mit H2 .